Impact of temperature on performance of series and parallel connected mono-crystalline silicon solar cells. (November 2015) - Chander, Subhash; Purohit, A.; Sharma, Anshu; Nehra, S.P.; Dhaka, M.S.
Abstract: This paper presents a study on impact of temperature on the performance of series and parallel connected mono-crystalline silicon (mono-Si) solar cell employing solar simulator. The experiment was carried out at constant light intensity 550 W/m 2 with cell temperature in the range 25–60 o C for single, series and parallel connected mono-Si solar cells. The performance parameters like open circuit voltage, maximum power, fill factor and efficiency are found to decrease with cell temperature while the short circuit current is observed to increase. The experimental results reveal that silicon solar cells connected in series and parallel combinations follow the Kirchhoff's laws and the temperature has a significant effect on the performance parameters of solar cell.